PROFIL ANALISIS BATU SALURAN KENCING DI INSTALASI LABORATORIUM KLINIK RSUP SANGLAH DENPASAR - Rasmika Dewi, Dewa Ayu Putu; Ngurah Subawa, Anak Agung (journal of internal medicine, 2007)
Urolithiasis is a pathological condition that is caused by the formation of hard mass like stone along theurinary tract. Identification of the urinary stones can be done through chemical analysis or using of infraredspectroscopy. The semiquantitative methods used to analyze are titrimetric and colorimetric. This study wascross sectional whose results were descriptive. The data used in this study was 113 urinary stone analysisrecords taken from Routine Clinic of Laboratory Clinic Installation at Sanglah Hospital in period January untilDecember 2007 (one year). The prevalence of urolithiasis in males were more than females (4:1) and it wasmostly occur in age range 40-60 years old of both sexes. Generally, more than one kind of stone compositionswere found in a patient of urolithiasis, the dominant was calcium oxalate.